The Poor always pay back : The Grameen II story - Dowla, Asif; Barua, Dipal (Bloomfield, CT : Kumarian Press, 2006)
This book is an introduction to Grameen II, an improved and flexible version of the classical Grammen model that is currently used to financially empower the poorest families in more than a hundred countries across the globe through savings and loans.
Introduction -- Classical Grameen and its impacts -- Loan products under Grameen II -- Savings mobilization : from one taka to 3000 billion taka -- Archeology of Grameen II -- Staff incentives and implementation of Grameen II -- The education loan and a program for the poorest -- Conclusion.
Includes bibliographical references (p. 265-278) and index.
osa 08/05/13
Loans
Keywords: Microfinance -- Developing countries; Poor -- Services for -- Developing countries; Grameen Bank